2006
DOI: 10.1111/j.1399-0039.2006.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the maternal 14‐bp insertion polymorphism in the HLA‐G gene in women with recurrent spontaneous abortions

Abstract: Human leukocyte antigen (HLA)-G has been postulated as an important immunotolerant molecule in maintaining fetal-maternal relationship. Recent reports indicated that the 14-bp deletion/insertion polymorphism in exon 8 of HLA-G gene influences HLA-G mRNA stability and isoform splicing patterns, thus modulating the levels of HLA-G expression. This might play an immunomodulatory role of HLA-G during implantation and pregnancy. In the present study, 109 unrelated fertile control women and 79 women who had experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
4
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 21 publications
(25 reference statements)
3
35
4
2
Order By: Relevance
“…According to Yan et al (2006), a significantly different distribution of the 14-bp genotype exists among Chinese, Danish and Indian RM populations and the discrepancy may be a result of ethnic variation (see Table 3). When compared to these other ethnic groups, several trends, however, do persist.…”
Section: Discussionmentioning
confidence: 99%
“…According to Yan et al (2006), a significantly different distribution of the 14-bp genotype exists among Chinese, Danish and Indian RM populations and the discrepancy may be a result of ethnic variation (see Table 3). When compared to these other ethnic groups, several trends, however, do persist.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, 4 studies were excluded due to duplicate publications [32][33][34][35], three had incomplete data on allele and genotype frequency which we failed to get by emails to the corresponding authors [36][37][38], and an additional one was excluded due to the absence of a control group [39]. Consequently, the remaining 17 case-control studies which examined the association between the HLA-G 14-bp polymorphism and RM were finally included [12,17,[25][26][27][40][41][42][43][44][45][46][47][48][49][50][51] (Fig. 1).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…Association between RM and HLA-G 14-bp insertion/deletion polymorphism allele Sixteen studies were included in assessing the association between HLA-G 14-bp insertion/deletion polymorphism allele and RM [12,17,[25][26][27][40][41][42][43][44][45][46][47][48][49][50]. As shown in Fig.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a 100% presence of HLA-G*010401 was seen in the 11 abortion cases, while it was present in only 51.9% of the cases that were a success. [77] In 2006, a Chinese team could not find the association between HLA-G and RSA; [78,79] also, a Polish study failed to do so, [80] albeit the team suggested that nonsignificance was probably due to the small sample size. [81] Two other negative studies were published -one in 2010 that analyzed 143 RSA and 150 control couples in the Indian population [82] and another one in 2012 on an Iraqi population of 50 RSA and 50 control women.…”
Section: "Wrong" Hla Programmingmentioning
confidence: 99%